2015
DOI: 10.1002/jcb.25402
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Regulates Renal Extracellular Matrix Deposit via Increased CTGF in Diabetes Mellitus

Abstract: Extracellular matrix accumulation and fibrosis are the features of diabetic nephropathy. PI3K (phosphatidylinositol 3-kinase)/Akt (protein kinase B) signal pathway and its inhibitor PTEN (phosphatase and tensin homolog deleted on chromosome 10) are revealed to modulate renal fibrosis. However, the exact mechanism is still not well known. In the present study we found that compared with normal mice, diabetic mice showed decreased PTEN, increased phospho-Akt (Ser 473), phospho-Akt (Thr 308), CTGF (connective tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
(29 reference statements)
5
27
0
Order By: Relevance
“…Monocytes are involved not only in acute inflammation but also in glomerulosclerosis, a feature common to both immune and non-immune forms of progressive renal disease (40). Collectively, these data are in line with reports showing increased MCP-1 production and FN accumulation by CTGF (41, 42). …”
Section: Discussionsupporting
confidence: 92%
“…Monocytes are involved not only in acute inflammation but also in glomerulosclerosis, a feature common to both immune and non-immune forms of progressive renal disease (40). Collectively, these data are in line with reports showing increased MCP-1 production and FN accumulation by CTGF (41, 42). …”
Section: Discussionsupporting
confidence: 92%
“…PI (3,4,5) P3 initiates a variety of signaling cascades by interacting with pleckstrin homology (PH) domain-containing proteins, most notably the serine kinase Akt [Vanhaesebroeck et al, 2010]. Similarly, in a previous study, we also demonstrated that the PI3K/Akt pathway was activated, including the full phosphorylation of Akt at Thr 308 and Ser 473, to increase the level of transforming growth factor-b1 (TGF-b1) protein and ECM accumulation in high glucose-treated renal tubular cells [Zhu et al, 2016]. Therefore, approaches to inhibit the activation of the PI3K/Akt pathway may become therapeutic points to prevent renal injuries from diabetes mellitus.…”
supporting
confidence: 59%
“…Previous studies showed a relationship between the PTEN/Akt pathway and heart fibrosis [36]. Some evidence directly illustrated that PTEN regulated renal fibrosis during diabetes mellitus [37]. At present, there are few studies regarding PTEN involvement in AKI-induced renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%